Attitudes and Beliefs Towards Ration Planning Among German Organic Pig and Poultry Farmers - Margret Krieger; Susanne Hoischen-Taubner; Leonie Blume; Albert Sundrum (Animals)
Providing young monogastric animals with the essential amino acids they need is challenging in organic feeding. The nutrient content of organic feeds varies widely, and additives are restricted, so feed rations must be formulated based on analysis. A survey of 56 organic pig and poultry farmers in Germany was carried out to investigate their attitudes towards ration planning and to examine and evaluate the feeding management on their farms. Principal component analysis was used to characterise the different attitudes. Cluster analysis revealed three groups: Farmers in Group 1 (n = 28) were uncertain about the nutrient requirements of organic animals. They accepted the importance of need-based feeding for health and performance, but did not recognise the importance of regular ration adjustments and were uncertain about the animals’ ability to compensate for deficiencies. In Group 2 (n = 11), need-based feeding and regular ration adjustments were most important to farmers, who were more likely to have professional feeding systems. In Group 3 (n = 17), farmers were least uncertain about nutrient requirements and did not believe that animals would lower their demand when undersupplied. Although the importance of need-based feeding was recognised, regular ration adjustment was of little importance for this group. Across all farms, 60% of the feed rations examined deviated significantly from recommendations. It is concluded that organic farmers need more guidance and perhaps pressure to fulfil their responsibility to provide their animals with the nutrients they need.